Fiscal Illusion and Fiscal Obfuscation:An Empirical Study of Tax Perception in Sweden - Tino Sanandaji; Björn Wallace (Research Institute of Industrial Economics (IFN), 2010)
In this paper we present survey evidence suggesting that there exists a sizeable fiscal illusion amongst the general public in Sweden. Respondents in a nation-wide and representative survey systematically underestimate the share of an ordinary workers income that is transferred to the public sector. Furthermore, we make a theoretical distinction between tax illusion and fiscal obfuscation, a proposed novel type of fiscal illusion. It has previously been assumed that fiscal illusion derives from a fragmentized tax system with many small, and largely invisible, taxes which tend to be ignored or underestimated by the tax payers. We hypothesize that this systematic bias could in addition emanate from misapprehensions of the real incidence of a tax. Evidence is presented that this could apply even when taxes are few and large, contrary to the tax complexity hypothesis. When this misperception derives from seemingly deliberate tax design and tax labeling, as appears to be the case with the payroll taxes in Sweden, we call it fiscal obfuscation.
Keywords: H11; H22; H24; H30; 330; Fiscal Illusion; Fiscal Obfuscation; Tax Illusion; Tax Labeling; Tax Structure; Personal Income Taxation; Fiskalillusion; Steuerinzidenz; Einkommensteuer; Schweden